MEREKONSTRUKSI PARADIGMA KESEMPURNAAN KRISTEN (PENATUA & DIAKEN) MELALUI PERSPEKTIF JOHN WESLEY - Pongoh, Daniel Willy; Palempung, Rivay (STT Kingdom, 2026)
This article examines the concept of Christian Perfection according to John Wesley and its relevance to the life and ministry of church officers in the GMIM Gloria Taratara congregation. The main issue addressed is the moral and spiritual crisis among church officers, particularly cases of adultery that contradict the Christian calling and the ethical demands of ministry. This study aims to analyze the gap between Wesley’s teaching on Christian Perfection and the lived reality of church officers, as well as to propose a renewed paradigm for church ministry. A qualitative research approach was employed, using interviews with church officers and congregation members, combined with theological literature analysis. The findings reveal that many church officers understand ministry merely as a formal ecclesial duty, lacking a deeper awareness of Christian Perfection as a lifelong process of sanctification rooted in perfect love. The study concludes that Wesley’s concept of Christian Perfection needs to be reconstructed as a communal process supported by spiritual formation, church discipline, and accountability systems, so that ministry may authentically reflect Christ’s love, holiness, and moral integrity within the contemporary church context.